Novel Treatment Strategies for Primary Biliary Cholangitis - Parés, Albert (Seminars in Liver Disease, 2017)
Despite the presumed immunological pathogenesis of primary biliary cholangitis, no clear or even harmful consequences have resulted from treatments designed to modify the immunological condition. Ursodeoxycholic acid (13–16 mg/kg/d) has, however, clear favorable effects that not only improve biochemical cholestasis, but also delay histological progression. Long-term treatment with ursodeoxycholic acid is associated with excellent transplant-free survival in cases showing a biochemical response at 1 year. Data on the effects of obeticholic acid and fibrates are encouraging. Moreover, recent pilot studies evaluating several biological agents targeting immunity such as different monoclonal antibodies and other drugs that modulate cholestasis are under investigation, although with limited results at present.
Keywords: ursodeoxycholic acid; fibrates; budesonide; obeticholic acid